Psychological Health, Sleep Quality, Behavior, and Internet Use Among People During the COVID-19 Pandemic: A Cross-Sectional Study - Elhadi, Muhammed; Alsoufi, Ahmed; Msherghi, Ahmed; Alshareea, Entisar; Ashini, Aimen; Nagib, Taha; Abuzid, Nada; Abodabos, Sanabel; Alrifai, Hind; Gresea, Eman; Yahya, Wisal; Ashour, Duha; et al. (Frontiers in Psychiatry, 2021)
Background The COVID-19 pandemic has led to an increase in the risk of suicide, uncertainty, mental stress, terror, annoyance, weariness, financial issues, and frustration. We aim to determine the prevalence of insomnia, depressive and anxiety symptoms, and their associated factors among Libyan populations during the COVID-19 pandemic and the civil war. Methods An online cross-sectional survey was conducted among the Libyan population between July 18 and August 23, 2020. This study assessed the psychological status of participants who were screened for anxiety symptoms using the seven-item Generalized Anxiety Disorder scale (GAD-7). Depressive symptoms were also screened for using the two-item Patient Health Questionnaire (PHQ-2) and the Insomnia Severity Index (ISI). Binomial logistic regression was used to predict the probability of insomnia, anxiety and depressive symptoms. Results A total of 10,296 responses were recorded. Among the participants, 4756 (46.2%) obtained a cut-off score of ≥ 3 which indicated depressive symptoms. For anxiety, 1,952 participants (19%) obtained a cut-off score of ≥ 15, which indicated anxiety symptoms. For the ISI, the mean (SD) was 11.4 (6.1) for the following categories: no clinical insomnia (0–7) 3132 (30.4%), sub-threshold insomnia (8–14) 3747 (36.4%), moderate severity clinical insomnia (15–21) 2929 (28.4%), and severe clinical insomnia (22–28) 488 (4.7%). Logistic regression analysis showed that depressive symptoms were statistically associated with age, marital status, education level, occupational category, financial problems during the COVID-19 pandemic, health status, having a COVID-19 infection, current health status, suicide ideation, abuse or domestic violence, and lockdown compliance (p < 0.05). The regression analysis revealed a statistically significant association between anxiety symptoms and age, education level, occupational status, financial problems during the COVID-19 pandemic, having a COVID-19 infection, health status, suicide ideation, abuse or domestic violence, and lockdown compliance (p < 0.05). The regression analysis revealed a statistically significant association between insomnia and all study variables with the exception of age, educational level, and occupational status (p < 0.05). Conclusion Policymakers need to promote effective measures to reduce mental health issues and improve people’s quality of life during the civil war and the COVID-19 pandemic.